2001
DOI: 10.1023/a:1015277619421
|View full text |Cite
|
Sign up to set email alerts
|

The Valuation of Insurance under Uncertainty: Does Information about Probability Matter?

Abstract: In a laboratory experiment we test the hypothesis that consumers' valuation of insurance is sensitive to the amount of information available on the probability of a potential loss. In order to test this hypothesis we simulate a market in which we elicit individuals' willingness to pay to insure against a loss characterised either by known or else vague probabilities. We use two distinct treatments by providing subjects with different information over the vague probabilities of loss. In general we find that unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Few early general experiments have reported the presence of ambiguity preference (see, for example, Heath and Tversky, 1991;Hogarth and Einhorn, 1990;Fox and Tversky, 1995). More recently, Wakker et al, (2003) and Di Mauro and Maffioletti (2001b) have shown that individuals may be ambiguity prone and not only ambiguity averse in an insurance context. This seems especially true when subjects make a comparison between something that they do know and something that they do not know much about.…”
Section: Implications For Trade Union Behaviourmentioning
confidence: 99%
“…Few early general experiments have reported the presence of ambiguity preference (see, for example, Heath and Tversky, 1991;Hogarth and Einhorn, 1990;Fox and Tversky, 1995). More recently, Wakker et al, (2003) and Di Mauro and Maffioletti (2001b) have shown that individuals may be ambiguity prone and not only ambiguity averse in an insurance context. This seems especially true when subjects make a comparison between something that they do know and something that they do not know much about.…”
Section: Implications For Trade Union Behaviourmentioning
confidence: 99%
“…Einhorn and Hogarth (), Hogarth and Kunreuther () and Di Mauro and Maffioletti () all find results compatible with the switching behaviour implied by the theory. Nevertheless, Di Mauro and Maffioletti () do not conclude that the majority of subjects exhibit switching behaviour.…”
Section: Results About Theories Of Decision Making Under Risk Uncertmentioning
confidence: 57%
“…An important difference between the two sets of findings is that Einhorn and Hogarth () and Hogarth and Kunreuther () utilized hypothetical incentives, whereas Di Mauro and Maffioletti () conduct an incentivized experiment. Di Mauro and Maffioletti () find a significant effect of ambiguity in an incentivized experiment as well, although they stipulate that the effect is weaker than that found in the earlier studies. Therefore, the saliency of the impact of ambiguity may decline when real incentives are used, possibly because individuals make a greater effort in calculating actual probabilities when there is something to be lost.…”
Section: Results About Theories Of Decision Making Under Risk Uncertmentioning
confidence: 88%
See 2 more Smart Citations